Application of [001]-textured (K, Na)(Nb, Sb)O3-CaZrO3 thick films to piezoelectric energy harvesters. Issue 13 (1st July 2022) - Chae, Seok-June; Na, Ji-won; Kim, Dae-Su; Kim, Sun-Woo; Go, Su-Hwan; Kim, Hero; Kim, Eun-Ji; Eum, Jae-Min; Nahm, Sahn
Abstract: A (K, Na)NbO3 (KNN)-based lead-free piezoceramic for a piezoelectric energy harvester (PEH) should exhibit a large k ij, Q m, d ij, and a small ε T 33 to generate a large power output. Texturing was used to enhance the piezoelectricity of KNN-related piezoceramics. In particular, the k ij and d ij values of the KNN-based piezoceramics were considerably improved after texturing along the [001] direction, with a small change in the ε T 33 /ε 0 value, indicating that the [001]-textured KNN-based thick films are good candidates for use in PEHs. The 0.97(K0.5 Na0.5 )(Nb0.93 Sb0.07 )O3 -0.03CaZrO3 [KN(N0.93 S0.07 )-CZ] thick film was textured along the [001] direction, and this thick film exhibited a large k p (0.57) and d 33 × g 33 (25.7 pm 2 /N), which is the largest d 33 × g 33 of the KNN-based piezoceramics reported to date. A cantilever PEH fabricated using the textured KN(N0.93 S0.07 )-CZ thick film exhibited a power density of 21.4 μW/mm 3 at the resonance frequency. This is the highest power density observed for PEHs fabricated using lead-free piezoceramics. The PEH also exhibited a power density of 0.023 μW/mm 3 at the off-resonance frequency. Therefore, the textured KN(N0.93 S0.07 )–CZ thick film is a good candidate for use in PEHs.